Early weaning of the child of a teenage mother (Research, Society and Development, 2022)
Based on the problem of early weaning in children of teenage mothers, this work aims to point out the increase in incidences, clarify the importance and advantages of exclusive breastfeeding for the baby up to the 6th month of life, and also that breastfeeding is diversified from according to several factors such as socioeconomic, psychosocial, cultural and belief. Depending on the characteristics of this teenage mother and the level of knowledge about the advantages that exclusive breastfeeding provides. It is up to nursing professionals to know how to identify the problems that have caused the increase in this incidence, and the frequent occurrence of this problem, and to provide continuing education from prenatal care to postpartum for these adolescent mothers and their families, encouraging them with evidence from mothers who exclusively breastfed until the 6th month of life, and the benefits they provided to their children. This is a research, with a quantitative approach, carried out at the Marfel family clinic and the Vasco Barcelos health post in the city of Nova Iguaçu. So, knowledge on this topic is of paramount importance for nursing professionals, which requires monitoring and evaluation of these adolescent nursing mothers and the extent to which the external influence of their families can help or hinder exclusive breastfeeding, essential performance of these professionals to seek strategies to try to minimize and remedy this problem, early weaning of children of teenage mothers.